Clinicopathological analysis of potentially malignant and malignant verrucopapillary lesions of the oral cavity – A literature review - Baishakhi Modak; Spoorti Kulkarni (Oral Oncology Reports)
Aims: This review article aims to provide an in-depth analysis of potentially malignant and malignant verrucopapillary lesions, including their etiology, clinical and histological features, differential diagnosis, and immunohistochemical analysis. Background: The word verrucopapillary lesions (VPL) refers to a variety of lesions in the oral region, ranging from benign to completely malignant tumors. They cause surface changes that can be seen as ulcerative, vesiculobullous, or papillary/papular/polypoid lesions, altering the usual morphology and stability of the mucosa. Review results: The clinical, histopathological and immunohistochemical characteristics of oral verrucopapillary lesions may help in their accurate diagnosis. Clinical significance: Verrucous and papillary lesions of the oral cavity are diagnostically challenging because of similar clinical presentation. The current understanding of potentially malignant VPLs is perplexing due to numerous terminologies. Many of the controversies in these entities are due to the lack of consensus on the disease characteristics and management.